2016
DOI: 10.1371/journal.pone.0165878
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Variations in Cervical Cancers in Indian Patients

Abstract: There are very few reports that describe the mutational landscape of cervical cancer, one of the leading cancers in Indian women. The aim of the present study was to investigate the somatic mutations that occur in cervical cancer. Whole exome sequencing of 10 treatment naïve tumour biopsies with matched blood samples, from a cohort of Indian patients with locally advanced disease, was performed. The data revealed missense mutations across 1282 genes, out of 1831 genes harbouring somatic mutations. These missen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It is previously found that the members of the ZNF family interact with nucleic acids, proteins, and small molecules and are involved in a variety of crucial molecular processes in cervical tumor cells at replication, transcriptional, and translational levels. Thus, ZNF605 and ZNF266 may be potentially targetable ( Das et al, 2016 ; The Cancer Genome Atlas Research Network, 2017 ; Li et al, 2018 ). OSTC can regulate gamma-secretase ( Wilson et al, 2011 ) while this secretase affects the ability of HPV pseudo-viruses infection in both human HaCat cells and mouse cells ( Huang et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is previously found that the members of the ZNF family interact with nucleic acids, proteins, and small molecules and are involved in a variety of crucial molecular processes in cervical tumor cells at replication, transcriptional, and translational levels. Thus, ZNF605 and ZNF266 may be potentially targetable ( Das et al, 2016 ; The Cancer Genome Atlas Research Network, 2017 ; Li et al, 2018 ). OSTC can regulate gamma-secretase ( Wilson et al, 2011 ) while this secretase affects the ability of HPV pseudo-viruses infection in both human HaCat cells and mouse cells ( Huang et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the emergence of tumor targeting drugs such as tyrosine kinase inhibitors, targeting the tumor based on its genomic profile rather than its histological background, it is important to study the prevalence of targetable oncogenic driver mutations throughout diverse ethnical cancer populations from diverse geographic areas. The prevalence of somatic mutations in cervical cancer was investigated previously in other cervical cancer cohorts worldwide from the US (N=80) [21], Norway/Mexico (N=100/15) [12], China (N=285) [23], the Netherlands (N=301) [20], France (N=29) [25], Hong Kong (N=15) [22], Guatemala/Venezuela/Mexico (N=280/40/325) [24], to India (N=10) [26], using varying techniques, from whole genome and/or exome sequencing [12,13,26], direct sequencing [23], to oncopanel analysis [20,21,25] or a combination of techniques [22,24]. This is the first study to describe the prevalence of driver mutations in an Indonesian cervical cancer cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower frequencies were also described in Norway (15%) and China (12%) [12,23]. And in a recent study from India, whole exome sequencing was performed on 10 FIGO stage 3b SCCs, with no PIK3CA mutations detected at all [26]. PIK3CA mutations lead to an altered production of the catalytic subunit p110α of the enzyme phosphatidylinositol 3-kinase (PI3K), allowing the PI3K pathway to signal without regulation, leading to uncontrolled cell growth, proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is previously found that the members of the ZNF family interact with nucleic acids, proteins and small molecules and are involved in a variety of crucial molecular processes in cervical tumor cells at replication, transcriptional and translational levels. Thus, ZNF605 and ZNF266 may be potentially targetable[87][88][89]. OSTC can regulate gamma-secretase[90] while this secretase affects the ability of HPV pseudo-viruses infection both in human HaCat cells and mouse cells[91].In summary, compared with the tests via individual prediction methods, it is demonstrated that HMP greatly improves statistical power by combining dependent…”
mentioning
confidence: 99%